Determinants of electronic cigarette use among vocational students in Buriram province, Thailand: an examination of behavioral and environmental influences: 10.55131/jphd/2024/230106 - Ruanphet, Kitipong; Jatuporn Luangubol; Sumattana Klangkarn (Journal of Public Health and Development, 2024)
The increasing prevalence of electronic cigarette use among adolescents is a global concern, particularly due to misconceptions about their safety. This study aims to explore the factors influencing e-cigarette smoking behavior among vocational students in Buriram Province, Thailand. This cross-sectional descriptive study involved 1,434 vocational students from Buriram vocational colleges, selected using a multi-stage sampling method. Data were collected through questionnaires addressing personal information, perceptions of e-cigarette harm, stress, depression, social support, and media influence. Binary logistic regression was used to identify factors associated with e-cigarette use. The study found that 34.9% of the participants had engaged in e-cigarette smoking. Significant factors associated with e-cigarette use included low grade point average (AOR=1.76; 95% CI: 1.282-2.424), peer e-cigarette smoking (AOR=4.39; 95% CI: 3.167-6.101), family member e-cigarette smoking (AOR=1.70; 95% CI: 1.130-2.576), being persuaded by friends (AOR=2.08; 95% CI: 1.566-2.775), easy access to e-cigarettes (AOR=1.98; 95% CI: 1.488-2.634), smoking marijuana (AOR=8.93; 95% CI: 5.961-13.398), and visiting entertainment venues (AOR=2.33; 95% CI: 1.714-3.170). Protective factors included being male (AOR=0.32; 95% CI: 0.206-0.525) and e-cigarette education in schools (AOR=0.60; 95% CI: 0.402-0.920). E-cigarette smoking among vocational students is influenced by multiple factors, including peer and family behaviors, academic performance, and social environments. Effective prevention programs must address these factors comprehensively. Policy Applications: The findings suggest the need for targeted interventions in schools and communities to reduce e-cigarette use among adolescents. Policies should focus on enhancing educational programs about the risks of e-cigarettes, restricting access, and engaging parents and peers in prevention efforts. Additionally, regulations to control the online sale and advertisement of e-cigarettes should be strengthened to mitigate their accessibility to youth.